Bile acid sequestrants in poor healing after endoscopic therapy of Barrett's esophagus - Lukas Welsch; Andrea May; Tobias Blasberg; Jens Wetzka; Elisa Müller; Myriam Heilani; Mireen Friedrich-Rust; Mate Knabe (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Endoscopic therapy for neoplastic Barrett's esophagus (BE) has become the standard of care over the past two decades. In clinical practice, we regularly encounter patients who fail to achieve complete squamous epithelialization of the esophagus. Although the therapeutic strategies in the individual stages of BE, dysplasia, and esophageal adenocarcinoma are well studied and largely standardized, the problem of inadequate healing after endoscopic therapy is only marginally considered. This study aimed to shed light on the variables influencing inadequate wound healing after endoscopic therapy and the effect of bile acid sequestrants (BAS) on healing. Methods Retrospective analysis of endoscopically treated neoplastic BE in a single referral center. Results In 12.1% out of 627 patients, insufficient healing was present 8 to 12 weeks after previous endoscopic therapy. The average follow-up duration was 38.8±18.4 months. Complete healing was achieved in 13 patients already after intensifying proton pump inhibitor therapy. Out of 48 patients under BAS, 29 patients (60.4%) showed complete healing. An additional eight patients (16.7%) improved, but only partial healing was achieved. Eleven (22.9%) patients showed no response to BAS augmented therapy. Conclusions In cases of insufficient healing even under exhaustion of proton pump inhibitors, treatment with BAS can be an option as an ultimate healing attempt.